A new species of Characidium Reinhardt (Characiformes: Crenuchidae) with a unique mid-water behavior from the upper rio Madeira basin, Brazil - Flausino, Nelson Junior; Lima, Flávio C.t.; Machado, Francisco A.; Melo, Marcelo R.s. (Zootaxa, 2020)
A new species of Characidium is described from headwater tributaries of the upper rio Guaporé, Rio Madeira basin, Mato Grosso state, Brazil. The new species can be diagnosed from all congeners, except Characidium summus, for lacking the preorbital and postorbital stripes. It can be diagnosed from the latter species by having 12 circumpeduncular scales (vs. 14), by an adipose fin present (vs. adipose fin absent), and 10–12 bars along the body (vs. absence of bars), among other characters. The new species is so far only known from direct tributaries of the Rio Guaporé at the Serra da Borda, an isolated plateau 300–800 meters above sea level, and possess a behavior very uncommon within the genus, being a mid-water pelagic fish, instead of the benthic behavior of most congeners. Comments on the putative phylogenetic relationships of the new species, as well as some remarks on its unusual behavior within the genus, are presented.